EXPERIENCES OF USING AUTOMATED ASSISTANT BOTS IN THE PEDAGOGICAL PROCESS - Ashurov Jasur Dzhoraevich; Hamroyev Bobirjon Bahritdinovich (The latest news and research in education, 2025)
This thesis discusses the role of automated assistant bots in the modern education system, methodological approaches to their implementation, and experiences of their use in real educational practice. The effectiveness of automating and interactivating certain elements of the educational process through bots created on the basis of Telegram, Microsoft Teams, and other platforms is analyzed.